Manufacture Indicator Paper for BSL or Small Bungur Extract (Lagerstroemia Indica L) as an Indicators Alternative of Acid-Base - Sri H. V. Pulukadang; Magfira (Universitas Tadulako, 2022)
This study aims to utilize extracts of local cherry blossoms or small bungur (Lagerstroemia Indica L) in the manufacture of indicator paper as an alternative acid-base indicator. Local Cherry Blossoms were macerated with methanol for ± 2 hours. Extracts and indicator paper of local cherry blossoms were tested as indicators in an acid-base solution, the buffer was then compared with phenolphthalein and methyl orange indicators for acid-base titration, namely strong acid and strong base, weak acid and strong base and weak base and strong acid. The results obtained in this study are: local cherry blossom extract is brownish yellow, in a strong acid it is pink, in a strong base it is dark green, in a weak acid it is pale pink and in a weak base it is light green. The indicator paper of local cherry blossom extract in strong acid is light pink, a strong base is yellow, a weak acid is pale pink, and a weak base is light green. In the buffer, the indicator paper of local cherry blossom extract has a pH range of 4-5 colors (pink-green), and 7-11 colors (yellow-green), the stability of the indicator paper from filter paper can maintain its color for 25 days. The type of acid-base titration that is suitable for the use of local cherry blossom extract indicators, precisely in the titration of strong acid-strong base and the weak acid-strong base is good to use as a substitute for phenolphthalein indicator, while in weak base-strong acid titration it is better to use as a substitute for methyl orange.